Health extension workers' level of job satisfaction in western Hararghe Zone, eastern Ethiopia: an institutional-based cross-sectional study - Aman, Kemal; Gobena, Tesfaye; Hawulte, Behailu; Maruta, Melat B.; Debella, Adera; Eyeberu, Addis; Abrahim, Rudwan; Wakjira, Olifan; Mussa, Ibsa (Frontiers in Health Services, 2024)
Background: There is a concern that job dissatisfaction among health extension workers (HEWs) reduces the benefit of investment in health extension program execution. Thus, the purpose of this study tried to explore the level of job satisfaction and factors affecting it among the HEWs in the West Hararghae Zone, Oromia Regional State, eastern Ethiopia.Method: An institutional-based cross-sectional study was conducted among 416 randomly selected health extension workers from September 20, 2020, to October 20, 2020. A pretested, structured questionnaire was used to collect the data. STATA 14.2 was used for data analysis.Bivariable and multivariable binary logistic regression analyses were also performed. Statistical significance was set at P < 0.05.Results: Health extension workers reported overall satisfaction of 51.8% (95% CI: 46.97%, 56.60%). Earning more than 5,260 ETB salary (AOR = 1.69, 95% CI: 1.01, 2.85), living more than 10 km from the district town (AOR = 1.59, 95% CI: 1.01, 2.53), receiving supportive supervision (AOR = 1.64, 95% CI: 1.06, 2.55), and not living with parents (AOR = 1.94, 95% CI: 1.24, 3.04) were significantly associated factors with HEW job satisfaction.Nearly half of health extension workers were dissatisfied with their jobs. Supportive supervision, compensation, distance, and parental home location were all predictors of job satisfaction. It is critical to establish intervention tactics that may satisfy and motivate HEWs to expand health coverage, strengthen health extension programs, and improve service delivery.